Stanley Hollander's T-shirt test: where marketing history meets psychogeography. (20th February 2017) - Brown, Stephen
Abstract : Purpose: The aim of this overview is to reflect on the family resemblances between psychogeography and marketing history. Design/methodology/approach: The paper is informally predicated on the perspectives and philosophies of literary theory in general and New Historicism in particular. Findings: Using exemplar excerpts from salient published works, marketing's hitherto overlooked psychogeographical traditions are contemplated and celebrated, the sterling contributions of Stanley C. Hollander above all. Research limitations/implications: Like poets who don't know it, marketing historians are unsung contributors to the psychogeographical corpus. There is much more that can be done, however, especially in relation to works of imaginative literature. Originality/value: This paper aims to uncover past achievements not advance the future agenda.